2023
DOI: 10.1007/s00261-023-03834-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving detection performance of hepatocellular carcinoma and interobserver agreement for liver imaging reporting and data system on CT using deep learning reconstruction

Abstract: Purpose This study aimed to compare the hepatocellular carcinoma (HCC) detection performance, interobserver agreement for Liver Imaging Reporting and Data System (LI-RADS) categories, and image quality between deep learning reconstruction (DLR) and conventional hybrid iterative reconstruction (Hybrid IR) in CT. Methods This retrospective study included patients who underwent abdominal dynamic contrast-enhanced CT between October 2021 and March 2022. Arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Thus, DLR with higher reconstruction strength appears suitable for CTHA during TACE. The qualitative score for tumor contrast was better on DLR-S than on DLR-M and hybrid-IR, which is consistent with a previous report that showed that DLR improved HCC detection on abdominal CT [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, DLR with higher reconstruction strength appears suitable for CTHA during TACE. The qualitative score for tumor contrast was better on DLR-S than on DLR-M and hybrid-IR, which is consistent with a previous report that showed that DLR improved HCC detection on abdominal CT [24].…”
Section: Discussionsupporting
confidence: 91%
“…MBIR images show high spatial resolution and low image noise [21,22], and therefore, AiCE also results in low image noise, good edge preservation, and good image detail preservation. In this study, DLR significantly decreased the SD of CT values in subcutaneous fat tissue and improved the qualitative scores for image granulation and artifact, indicating that DLR [23,24]. We also found that DLR significantly increased the CT values of hepatic arteries, which is in accord with a previous report on dynamic abdominal CT that found CT values to be increased with DLR [25].…”
Section: Discussionsupporting
confidence: 91%
“…12,16 DLR has been shown to reduce image noise and improves image quality compared to conventional Hybrid-IR and FBP. 10,17 Based on our study, it became evident that streak artifacts caused by arms alongside the torso could also be significantly reduced compared with Hybrid-IR and FBP using both the quantitative and qualitative analyses.…”
Section: Discussionmentioning
confidence: 73%
“…In supervised training of DLR, low-quality data and high-quality images are respectively used as the input and reference data. A trained DLR is known to reduce image noise [ 19 ], thereby improving the quality of CT images in regions as varied as the head [ 20 , 21 ], chest [ 9 ], abdomen [ 10 , 19 , 22 , 23 ], and vertebrae [ 11 , 24 , 25 ]. We therefore hypothesized that DLR can also improve the quality of high-resolution CT of the temporal bone.…”
Section: Introductionmentioning
confidence: 99%